2010
DOI: 10.1111/j.1537-2995.2010.02603.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute anemia in a Jehovah's Witness patient with acute lymphoblastic leukemia with polymerized bovine hemoglobin‐based oxygen carrier: a case report and review of literature

Abstract: This report documents the successful management of profound anemia in an acute leukemia patient who refused blood transfusion, with the use of Hemopure, to save the patient from the devastating effects of ischemia associated with severe anemia. Hemopure may represent a life-saving intervention in patients with severe symptomatic anemia when blood transfusion is not an option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
1
17
0
4
Order By: Relevance
“…The expected cost explosion in transfusion medicine resulting from an increasing imbalance between donors and recipients, and treatment of transfusion-associated complications, has increased the socio-economic significance of the development of safe and effective synthetic oxygen carriers as an alternative to the transfusion of allogeneic RBCs 139. However, a recent review of artificial oxygen carriers indicated that despite decades of preclinical and clinical research on them, the results were disappointing.…”
Section: Use Of Artificial Oxygen Carriersmentioning
confidence: 99%
“…The expected cost explosion in transfusion medicine resulting from an increasing imbalance between donors and recipients, and treatment of transfusion-associated complications, has increased the socio-economic significance of the development of safe and effective synthetic oxygen carriers as an alternative to the transfusion of allogeneic RBCs 139. However, a recent review of artificial oxygen carriers indicated that despite decades of preclinical and clinical research on them, the results were disappointing.…”
Section: Use Of Artificial Oxygen Carriersmentioning
confidence: 99%
“…Under the FDA's Expanded Access program, Hemopure has been used to treat severe anemia in JW patients after induction chemotherapy for leukemia, 36 burns, 37 trauma, 38 and autoimmune hemolytic anemia. 39 Hemopure or HBOCs are not a replacement for human allogeneic blood transfusion, but in cases of lifethreatening anemia in JW patients for which blood transfusion is not an option, it may be life-saving.…”
Section: Hbocsmentioning
confidence: 99%
“…11 The majority of these cases involved patients who were JWs. [6][7][8]10,11 Herein, we describe a case of severe anemia secondary to wAIHA in a patient who refused RBC transfusion on religious grounds. He was treated with Hemopure under a compassionate use protocol, in addition to high-dose steroids, while awaiting definitive treatment with splenic artery embolization.…”
mentioning
confidence: 99%